Reflection on the response of healthcare professionals to the COVID-19 pandemic-preclinical students identify what their profession is about - Prerna Agarwal; Dalia A Biswas (Journal of Medical Education Development)
Background & Objective: Medical professionalism and identity formation are typically learned through hands-on medical training and practice. But during the early COVID–19 pandemic, medical students were displaced from campus. However, they could engage with the characteristics of the profession by critically observing the response of healthcare professionals to the COVID–19 pandemic through news, such other means. and personal experience. The purpose of this study was to explore if preclinical students could discern the core values of their profession in such unusual circumstances. Material & Methods: The qualitative study, content analysis based on the principles of grounded theory, was conducted from October 2020 – January 2021, among the preclinical students of a medical college in India. After an online sensitization, they were asked to write reflection notes. The reflection notes of all 28 respondents were analysed thematically using QDA Miner Lite 2.0.5. Results: There were 28 respondents. An exhaustive number of 15 themes emerged from the analysis of their reflection notes that encompassed various aspects of the medical profession – ranging from good moral character attributes of a healthcare professional to hazards of the profession to the students taking pride in being associated with it. What is identified by a student as being important, may be expected to be learned better by them. Therefore, we may expect these students to have learned about the attributes of medical professionalism and identity formation, which they had identified through reflection, more meaningfully when they joined back Conclusion: Even while off campus, students likely continued to learn about their profession. It is reasonable to expect they may gain a deep understanding of their profession upon resuming their training on campus.